2005
DOI: 10.1182/blood-2004-07-2885
|View full text |Cite
|
Sign up to set email alerts
|

Sema4D induces angiogenesis through Met recruitment by Plexin B1

Abstract: Semaphorins, a large family of membranebound and secreted proteins, signal through their transmembrane receptors, the plexins. Semaphorins and plexins share structural homologies with scatter factor receptors, a family of tyrosine kinase receptors for which Met is the prototype. Semaphorins have been studied primarily in the developing nervous system, where they act as repelling cues in axon guidance. However, they are widely expressed in several tissues, and their role in epithelial morphogenesis has been rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
205
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(215 citation statements)
references
References 49 publications
4
205
0
3
Order By: Relevance
“…Among them, plexin-B1 is a receptor for Sema4D, and it has been reported that Sema4D-Plexin-B1 signaling promotes endothelial cell migration and tube formation [67,68]. Interestingly, Sema4D expression is upregulated in head and neck squamous cell carcinoma as well as in some other solid tumors [69,70].…”
Section: Pro-angiogenic Semaphorinsmentioning
confidence: 99%
“…Among them, plexin-B1 is a receptor for Sema4D, and it has been reported that Sema4D-Plexin-B1 signaling promotes endothelial cell migration and tube formation [67,68]. Interestingly, Sema4D expression is upregulated in head and neck squamous cell carcinoma as well as in some other solid tumors [69,70].…”
Section: Pro-angiogenic Semaphorinsmentioning
confidence: 99%
“…Notably, binding of Sema 4D to Plexin B1 transactivates the tyrosine kinase activity of cMet independent of the presence of HGF/SF [88]. Interestingly, the identical signaling pathway in endothelial cells leads to angiogenesis [89].…”
Section: C-met and Hepatocyte Growth Factor/scatter Factor (Hgf/sf)mentioning
confidence: 99%
“…Another study showed that Sema4D induces angiogenesis, which was mediated by the coupling of its high-affinity receptor plexin-B1 with the Met tyrosine kinase (Conrotto et al, 2005). In addition, class IV semaphorins frequently have PDZ {PSD (postsynaptic density protein) 95, DlgA (Discs large A), and ZO (zonula occludens) 1)} domain-binding motifs at their C-termini, through which they may function as receptors by mediating signal transfers through their intracellular domains.…”
Section: Clcp1 Regulates Lung Cancer Cell Motility With Sema4bmentioning
confidence: 99%